Brain tumours and exposure to pesticides: a case–control study in southwestern France. Issue 8 (30th May 2007) - Provost, Dorothée; Cantagrel, Anne; Lebailly, Pierre; Jaffré, Anne; Loyant, Véronique; Loiseau, Hugues; Vital, Anne; Brochard, Patrick; Baldi, Isabelle
Abstract : Background: Brain tumours are often disabling and rapidly lethal; their aetiology is largely unknown. Among potential risk factors, pesticides are suspected. Objective: To examine the relationship between exposure to pesticides and brain tumours in adults in a population-based case–control study in southwestern France. Methods: Between May 1999 and April 2001, 221 incident cases of brain tumours and 442 individually matched controls selected from the general population were enrolled. Histories of occupational and environmental exposures, medical and lifestyle information were collected. A cumulative index of occupational exposure to pesticides was created, based on expert review of lifelong jobs and tasks. Separate analyses were performed for gliomas and meningiomas. Results: A non-statistically significant increase in risk was found for brain tumours when all types of occupational exposure to pesticides were considered (OR = 1.29, 95% CI 0.87 to 1.91) and slightly higher but still non-statistically significant when gliomas were considered separately (OR = 1.47, 95% CI 0.81 to 2.66). In the highest quartile of the cumulative index, a significant association was found for brain tumours (OR = 2.16, 95% CI 1.10 to 4.23) and for gliomas (OR = 3.21, 95% CI 1.13 to 9.11), but not for meningiomas. A significant increase in risk was also seen for the treatment of home plants (OR = 2.24, 95% CI 1.16 to 4.30) owing to environmental exposure to pesticides. Conclusions: These data suggest that a high level of occupational exposure to pesticides might be associated with an excess risk of brain tumours, and especially of gliomas.